Analisis Persepsi Nasabah pada Pengguna Aplikasi BSI Mobile - Shifa Ani Aulia; Christian Wiradendi Wolor; Eka Dewi Utari (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The development of digital technology has driven a transformation in banking services, including Islamic banking. This study aims to analyze customer perceptions of the BSI Mobile application, focusing on security, stability, and service reliability. A qualitative approach with a case study design was used. Data were collected through social media observations, Google Play Store reviews, and in-depth interviews with four active users. Data were analyzed using the Miles and Huberman interactive model. The results revealed that system disruptions, slow transactions, and lack of transparency in complaint handling caused customer dissatisfaction. However, most pre-research respondents still trusted the app's security. Negative interactions on social media and user reviews influenced the app's image. Recommendations include improving app stability, customer service responsiveness, and proactive communication to rebuild customer trust.